ALTERNATIF PENGAJARAN KALIMAT SEDERHANA BAHASA JERMAN BERBASIS PENDEKATAN SAI NTIFIK - MURSALIN, (LATERNE, 2016)
The purpose of teaching the German language sentence is for students to be able to make a sentence correctly. If they are correct, the idea expressed they at least can be understood. So far the teaching of sentence served by asking the students pay attention to the rules (regal) and then practice until eventually asked to write their own sentences. Since the adoption of German sentences, the study aimed at learning scientific text.              Scientific Learning does not regard the learning outcomes as the estuary end game but the learning process is considered very important. Therefore the emphasis on the scientific learning process skills. Model-based learning science process skills improvement is learning model that integrates science process skills into the system in an integrated presentation of the material (Beyer, 1991). This model emphasizes the process of finding knowledge of the transfer of knowledge, the learner is seen as a subject of study that needs to be actively involved in the learning process, the teacher is only a facilitator, guide and coordinate the activities of learning.  Language learning German as a foreign language in particular makes the sentence, requiring approaches the situation with English characters. Indonesian different in order to express the idea / notion sentence. To that end, students are asked to be active in the process of making a sentence, so that they understand the stages that must be passed when writing sentences. The process is the key to doing a sentence. Teaching sentences involving students in the process is done with scientific begins with identifying, understanding, and build there to make sentences that described the activities of intact 5 M, namely (1) the stage of observing, (2) ask, (3) attempts, (4) associates, and (5) communicating. There are several requirements to make sentences like familiar word class, conjugation, Nomen, declination, functions SPOK and wording, which must be done before the students construct phrases. Therefore these stages is a stage / step instruction to make sentences. The method used in this research is descriptive qualitative. The learning model is designed on the theory of Scientific Approaches and theories of other supporters. These theories are taken from books and articles whose contents are relevant to these studies. Data collection techniques used is literature. Teaching steps indicate that the teaching of the German language simple sentence based scientific approaches to do. This is due to the involvement of students in the process of understanding the concept of sentences and elements of the establishment. Phase I and II is the stage students observe and identify. In stage III and IV students can refer to and understand the rules, functions and discussions that occur in the sentence. Recently students communicated, the phrase still reproductive stage.                The results of theoretical study teaching steps sentence load up activity, the core and the cover. While each step based scientific approaches with 5 M: to observe, ask, try, associate and communicate in research activities in the form of follow students. Keywords: Teaching, simple sentences, Scientific Approach.